2014
DOI: 10.1007/s00417-014-2688-1
|View full text |Cite
|
Sign up to set email alerts
|

Two-year visual outcome of ranibizumab in typical neovascular age-related macular degeneration and polypoidal choroidal vasculopathy

Abstract: Intravitreal ranibizumab significantly improved the VA initially, but this improvement did not persist at 2 years post-treatment. In PCV, ARMS2 A69S polymorphism is associated with the baseline and 12-month VA, but is not associated with the visual prognosis at 24 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
2
21
1
Order By: Relevance
“…The present study showed -0.13 and -0.03 logMAR unit changes in mean BCVA in tAMD and PCV patients, respectively, at 24 months after the initial IVR. The degree of BCVA improvement in tAMD patients was comparable or superior to that in previous reports, but only a modest improvement was seen in PCV patients [14,24,25,26]; hence, the improvement of BCVA at 3 and 24 months was significantly greater in tAMD than in PCV patients. Since there have been very few reports which conducted a direct comparison of the long-term outcomes of IVR between tAMD and PCV [9,14], the results in the present study may be useful when considering the indication of IVR in PCV cases.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The present study showed -0.13 and -0.03 logMAR unit changes in mean BCVA in tAMD and PCV patients, respectively, at 24 months after the initial IVR. The degree of BCVA improvement in tAMD patients was comparable or superior to that in previous reports, but only a modest improvement was seen in PCV patients [14,24,25,26]; hence, the improvement of BCVA at 3 and 24 months was significantly greater in tAMD than in PCV patients. Since there have been very few reports which conducted a direct comparison of the long-term outcomes of IVR between tAMD and PCV [9,14], the results in the present study may be useful when considering the indication of IVR in PCV cases.…”
Section: Discussionsupporting
confidence: 75%
“…Hence, the Japanese treatment guideline for AMD recommends different tactics depending on the phenotypes of AMD, in which tAMD is recommended to be treated with anti-VEGF monotherapy, whereas PCV may be treated with anti-VEGF therapy, photodynamic therapy (PDT) or combination therapy [13]. However, it is inconclusive as to whether or not these phenotypes of AMD are definitely associated with the effectiveness of IVR because there have only been few studies which conducted a direct comparison between tAMD and PCV regarding the outcomes of IVR [9,14]. Moreover, the factors associated with the visual prognosis of IVR treatments have not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…3 4 Therefore, like AMD, symptomatic PCV is treated by intravitreal injection of anti-VEGF agents such as pegaptanib, ranibizumab and aflibercept. 5 Photodynamic therapy (PDT) with or without intravitreal anti-VEGF therapy is also used to treat symptomatic PCV and has favourable effects on visual acuity (VA). [6][7][8] In the EVEREST study, the 6-month rate of complete polyp regression was higher for patients treated with PDT combined with intravitreal injection of ranibizumab (IVR) than in those treated with IVR alone (77.8% vs 28.6%, p<0.001).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies are the results of a relatively short follow-up period (4 months–1 year19,2729); therefore, the outcome in a longer follow-up period is still unclear. This is clinically very important because a short follow-up period is often not long enough to conclude the patients’ prognoses.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients with PCV show different responses to anti-VEGF treatments compared to the t-AMD patients 30,31. Although there were several investigations regarding the efficacy of switching to aflibercept for patients with PCV,19,2729 these studies had small sample sizes and were treated with a fixed-dosing procedure. Thus, the outcome of TAE aflibercept therapy for patients with PCV has not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%